Organization model compound by phases to establish didactic methodological actions in the scientific formation of the Weightlifting trainer - Luis Orlando Caballero-Riera; Leandro Hernández-Simón; Zulinma Martínez-Nariño (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2015)
The work offers a model with organization didactic methodological actions having the purpose of transforming the insufficiencies revealed in the scientific preparation of the Physical Culture and Sport Professional, as well as in the development and leading of the scientific investigative activity during the solution of problems that are shown in the socio professional context of the Weightlifting sport. The actions are focused in the scientific investigative activities and in the information management about the trainers leadership, having them to acting an independent and productive way; where the investigative creative activity articulated is harmonically with the development of investigative skills making possible the acquisition of capacities in the scientific investigative work. To carry out this research theoretical and empirical methods of investigation were used which allowed to base the proposed, to carry out the investigation process and to value its feasibility according to the specialists criteria for the solution of the Scientific Problem.